The Position of Customary Criminal Law in Positive Law in Indonesia - Hamid Noor Yasin; Ade Saptomo (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research explores the status of customary criminal law in the context of positive law in Indonesia. Customary criminal law, as an integral part of the cultural heritage of Indonesian society, has values and norms that have developed from generation to generation. However, in an era of increasingly structured positive law, fundamental questions arise regarding the extent to which customary criminal law is accommodated and recognized by the formal legal system. This research uses a normative legal approach to analyze statutory regulations, court decisions, and related legal literature. Research findings identify that although customary criminal law is not explicitly regulated in the national positive law system, there are certain efforts to recognize and respect its existence. In this context, this research explores the concept of integrating customary criminal law into a positive legal system as a medium of preserving legal plurality and realizing local justice. Apart from that, this analysis also discusses the challenges and potential conflicts between customary criminal law and modern positive law principles, as well as efforts that can be made to achieve harmony between the two. In conclusion, this research contributes to a better understanding of the status of customary criminal law in the context of positive law in Indonesia, by highlighting important aspects to be considered in developing inclusive and just legal policies. This research is in the form of a research article.